MARGALEF INDEX, SIMPSON INDEX AND SHANNON-WEAIVER INDEX CALCULATION FOR DIVERSITY AND ABUDANCE OF BEETLE IN TROPICAL FOREST - Ibnu Sina; Iskandar Zulkarnaen (Math Program, Math and Science faculty, Pamulang University, 2019)
Field sampling was conducted from July to August 2019 to determine the diversity and abundance of beetle fauna at Gayo Lues Forest, Takengon, Central Aceh. The study was conducted at two sites namely trail I and trail II. The beetles were sampled using 2 light traps, 2 malaise traps and 20 pitfall traps. Total of 219 beetle specimens comprising of 67 species from 24 families were collected. Light trap collected the most number of beetles (N=117) and Margalef index showed that the most abundant beetle was collected by light trap (Margalef index, 27.551). Shannon-Weiner index shows that the most specious beetle was caught by light traps (4.399). The results showed that the most efficient trap was light trapping. Trail I has the most abundance (Margalef Index: 18.572) but trail II was the most specious (Shannon Weiner Index: 4.176) beetle fauna, whereas trail II has the least abundance (Margalef Index: 17.295) and Campsite has least diverse (Shannon Weiner Index: 3.769).The most abundant family caught was Staphylinidae (Margalef index : 2.667) and specious beetle family caught was the Chrysomelida (Shannon Weiner : 1.846) followed by the ground beetle family Scarabaeidae (Shannon Weiver:1.828). Result of this findings showed that Gayo Lues Forest is an undisturbed forests and has been preserved well.Keywords : Beetle, Diversity, Abundance, Takengon, Gayo